2016
DOI: 10.1890/15-0787.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental simulation of pollinator decline causes community‐wide reductions in seedling diversity and abundance

Abstract: Abstract.Pollinator decline can disrupt the mutualistic interactions between plants and pollinators and potentially affect the maintenance of plant populations. However, there is still little knowledge on how changes in pollinator abundance can affect seedling recruitment, which is essential for population persistence. We experimentally simulated a community-wide reduction in pollinator availability during four years to examine its effects on seedling recruitment in 10 perennial herbs in a Norwegian hay meadow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 84 publications
2
25
0
4
Order By: Relevance
“…This finding may be explained by the fact that some plants need specific pollinators and therefore cannot produce seed set in a site where their pollinator does not occur (Steffan-Dewenter and Tscharntke 1999). More importantly, there was stronger evidence for an effect directed from bee to plant species richness, in line with other studies demonstrating that plant diversity benefits from increasing bee diversity ) and pollinator availability (Lundgren et al 2016). This result supports the idea of a more complex structure where individuals of multiple plant and pollinator species interact and indirectly affect each other (Carvalheiro et al 2014).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding may be explained by the fact that some plants need specific pollinators and therefore cannot produce seed set in a site where their pollinator does not occur (Steffan-Dewenter and Tscharntke 1999). More importantly, there was stronger evidence for an effect directed from bee to plant species richness, in line with other studies demonstrating that plant diversity benefits from increasing bee diversity ) and pollinator availability (Lundgren et al 2016). This result supports the idea of a more complex structure where individuals of multiple plant and pollinator species interact and indirectly affect each other (Carvalheiro et al 2014).…”
Section: Discussionsupporting
confidence: 89%
“…) and pollinator availability (Lundgren et al. ). This result supports the idea of a more complex structure where individuals of multiple plant and pollinator species interact and indirectly affect each other (Carvalheiro et al.…”
Section: Discussionmentioning
confidence: 99%
“…Plant interactions with animals, such as pollination, have a major role in determining species composition in communities (Sargent and Ackerly 2008). Many plant species depend on pollinators for their reproduction (Ollerton et al 2011), and can only persist in a community in the presence of such mutualists (Lundgren et al 2016). In this scenario, only the plant species with reproductive traits fitting the local pollinator community will persist, implying that pollinators act as biotic filters (Shrestha et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Using a different approach Albrecht et al (2012) showed that increased pollinator functional group richness resulted in greater fruit and seed set in a model plant, Raphanus sativus. At a larger ecological scale, Lundgren et al (2016) reduced pollinator availability at the community-level over four years and assessed how this affected recruitment of seedlings in 10 perennial hay meadow herbs in Norway. The results were complex and to some extent dependent upon the plant being studied, but over all the loss of pollinators resulted in a decline in the diversity and abundance of seedlings.…”
mentioning
confidence: 99%